Treating Waste with Waste : Utilization of Iron Powder for the Reduction of Chromium (Cr6+) in Metal Plating Industry Liquid Waste - Sunardi (Jurnal Serambi Engineering, 2024)
Metal plating industry waste is the main source of environmental pollution due to heavy metal chromium(Cr6+). The method commonly used in processing chromium metal waste (Cr6+) in industry is by means ofreduction and coagulation. Chromium metal (Cr6+) is highly toxic because it is highly unstable comparedto chromium (Cr3+). Therefore, chromium waste (Cr6+) must be reduced to chromium (Cr3+) before beingdischarged into the environment. The purpose of the study is to reduce the content of chromium ions (Cr6+)in liquid waste of the metal coating industry by the reduction and coagulation process using waste ironpowder and calcium hydroxide. Liquid chromium waste (Cr6+) and iron powder waste are taken from the metal coating industry in Palur Karanganyar, Central Java. Iron waste is in the form of powder that comesfrom the sanding process that is no longer used. The parameters studied were the weight of iron powder, the addition of H2SO4 2N, and the reduction time. The measurement of chrom ion levels (Cr6+) in all treatments was determined by UV-Vis Spectroscopy. The results of the study showed that the chromium level (Cr 6+) of liquid waste of the metal coating industry was 749 mg/L. Theoptimum condition for reducing chromium (Cr6+) is to use 3 gr iron powder, 10 ml of H2SO4 2N, and a reduction time of 7 minutes there is a decrease in chromium (Cr6+) levels by 100% with a chromium level (Cr6+) of 0 mg/L. This result meets the Regional Regulation of Central Java Province Number 5 of 2012 concerning Liquid Wastewater Quality Standards for the Metal Plating Industry which requires a maximum chromium level (Cr6+) of 0.1 mg/L.